KONSTRUKSI GAYA HIDUP MELALUI MUSIK SEBAGAI PRODUK BUDAYA POPULER - Glorya Agustiningsih (Jurnal Komunikasi dan Bisnis, 2018)
Business industry plays crucial role in establishing consumer preference to product consumption, either goods or services, by starting to plan and produce the design, form, model, style and marketing tactics to influence specific market segment for purchasing, consuming and behave that suits to product positioning. Likewise in music recording industry which in its early establishment had contributed in forming music genres also determines music trends that become indulgence of their fans in a period of time. Big music recording company particularly determines which music genre to be popularized, who is the artists, recording process, distribution and marketing communication strategies. An appropriate planning leads the recording company to be able to raise the selling and all at once also forming music as a popular culture product that communicates through communication mediums, and it is gradually being consumed and admired and able to construct their listeners behaviors. This behavior which is later being adopted as a lifestyle. Refer to this concept, the objective of this research is to describe how the music as a popular culture product constructs its audience lifestyle. Qualitative method using in-depth interview technique is the main method approached to collect data research. Results of this research is expected to benefit the future knowledge development of communication science, particularly to the practice of music recording industry.Keywords: Music, Lifestyle, Cultural Product, Popular Culture.